MANAJEMEN DAKWAH BAITUL MAL TAZKIA DALAM PENGEMBANGAN DAN PEMBERDAYAAN MASYARAKAT - Ulul Aedi; A Arsam; Asep Amaludin (MAMBA'UL 'ULUM, 2023)
Da'wah is an effort to change society for a better life. The purpose of da'wah is to create a prosperous, safe and prosperous life for the community. To achieve this goal, da'wah activities require careful planning. With careful planning the goals of da'wah will be more easily achieved. Da'wah planning must be based on community needs and oriented towards community welfare. It can be said, da'wah activities require management as a prerequisite for the success of their activities. This study aims to describe how Baitul Mal Tazkia applies da'wah management in the management of its institution. This research method is descriptive qualitative. This study obtains an overview of the da'wah management of the Baitul Mal Tazkia institution. The da'wah management of the Baitul Mal Tazkia institution applies four stages of management. Planning, organizing, implementing, and evaluating. In the Baitul Mal planning stage, Tazkia carries out the assessment process, data collection, HR preparation and program preparation. The organizing process is carried out by placing qualified and competent human resources in their fields. The implementation of the Baitul Mal Tazkia program can run well, in fact it is always growing every year. Evaluation is done by compiling an annual report. In addition, evaluation is also carried out through assistance carried out by Baitul Mal Tazkia.